Brucellosis in the Greater Yellowstone Area: Disease Management at the Wildlife–Livestock Interface - Brant A. Schumaker (Human-Wildlife Interactions, 2017)
Elk (Cervus elaphus) and bison (Bison bison) of the Greater Yellowstone area are the last known reservoir of bovine brucellosis (Brucella abortus) in the United States. Domestic cattle occasionally contract the disease while grazing in areas where infected wild ungulates have aborted their fetuses or have given birth. Cases of brucellosis in cattle trigger costly quarantine, testing, and culling procedures. Government agencies and stakeholders, therefore, allocate valuable resources to prevent wildlife-to-cattle transmission. Scientific uncertainty about the biology, epidemiology, and economics of brucellosis makes it difficult to determine the length to which society should go to control it or the combination of management activities they should use to achieve the desired level of control. Research over the last decade has generated new information about brucellosis and alternative approaches for management. Stakeholders and decision makers must synthesize this growing body of information and re-assess current brucellosis goals and management strategies. Economic principles provide an objective framework in which to do this.